Situation Report: Romania, 25 February 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Receives New Soviet Ambassador Pavel Stefan Re-Emerges Foreign Trade Conference at the Central Committee Polish-Romanian Writers Agreement Cultural Relations with Cuba National Construction Conference Opens State Council Meets Romania to Enter Geneva Auto Show